Answer:
(a) ![l = -w + 21](https://tex.z-dn.net/?f=l%20%3D%20-w%20%2B%2021)
(b) Domain:
<em>(See attachment for graph)</em>
(c) ![f(w) = -w + 21](https://tex.z-dn.net/?f=f%28w%29%20%3D%20-w%20%2B%2021)
Step-by-step explanation:
Given
![2(l + w) = 42](https://tex.z-dn.net/?f=2%28l%20%2B%20w%29%20%3D%2042)
![l = length](https://tex.z-dn.net/?f=l%20%3D%20length)
![w = width](https://tex.z-dn.net/?f=w%20%3D%20width)
Solving (a): A function; l in terms of w
All we need to do is make l the subject in ![2(l + w) = 42](https://tex.z-dn.net/?f=2%28l%20%2B%20w%29%20%3D%2042)
Divide through by 2
![l + w = 21](https://tex.z-dn.net/?f=l%20%2B%20w%20%3D%2021)
Subtract w from both sides
![l + w - w = 21 - w](https://tex.z-dn.net/?f=l%20%2B%20w%20-%20w%20%3D%2021%20-%20w)
![l = 21 - w](https://tex.z-dn.net/?f=l%20%20%3D%2021%20-%20w)
Reorder
![l = -w + 21](https://tex.z-dn.net/?f=l%20%3D%20-w%20%2B%2021)
Solving (b): The graph
In (a), we have:
![l = -w + 21](https://tex.z-dn.net/?f=l%20%3D%20-w%20%2B%2021)
Since l and w are the dimensions of the fence, they can't be less than 1
So, the domain of the function can be ![0](https://tex.z-dn.net/?f=0%20%3Cw%20%3C%2021)
--------------------------------------------------------------------------------------------------
To check this
When ![w = 1](https://tex.z-dn.net/?f=w%20%3D%201)
![l = -1 + 21](https://tex.z-dn.net/?f=l%20%3D%20-1%20%2B%2021)
![l = 20](https://tex.z-dn.net/?f=l%20%3D%2020)
![(w,l) = (1,20)](https://tex.z-dn.net/?f=%28w%2Cl%29%20%3D%20%281%2C20%29)
When ![w = 20](https://tex.z-dn.net/?f=w%20%3D%2020)
![l = -20 + 21](https://tex.z-dn.net/?f=l%20%3D%20-20%20%2B%2021)
![l = 1](https://tex.z-dn.net/?f=l%20%3D%201)
--------------------------------------------------------------------------------------------------
<em>See attachment for graph</em>
<em></em>
Solving (c): Write l as a function ![f(w)](https://tex.z-dn.net/?f=f%28w%29)
In (a), we have:
![l = -w + 21](https://tex.z-dn.net/?f=l%20%3D%20-w%20%2B%2021)
Writing l as a function, we have:
![l = f(w)](https://tex.z-dn.net/?f=l%20%3D%20f%28w%29)
Substitute
for l in ![l = -w + 21](https://tex.z-dn.net/?f=l%20%3D%20-w%20%2B%2021)
becomes
![f(w) = -w + 21](https://tex.z-dn.net/?f=f%28w%29%20%3D%20-w%20%2B%2021)
Answer:
1/27 is the answer
Step-by-step explanation:
It is 1/(3^3) which is 1/27
![\frac{28}{x^2} = \frac{7}{xy}](https://tex.z-dn.net/?f=%20%5Cfrac%7B28%7D%7Bx%5E2%7D%20%3D%20%5Cfrac%7B7%7D%7Bxy%7D%20)
multiplying both sides by x^2
![28=\frac{7x^2}{xy}](https://tex.z-dn.net/?f=%2028%3D%5Cfrac%7B7x%5E2%7D%7Bxy%7D%20)
simplifying
![28= \frac{7x}{y}](https://tex.z-dn.net/?f=28%3D%20%5Cfrac%7B7x%7D%7By%7D%20)
dividing by 7
x 55
-------- = ---------
69.50 100
69.50*55= 3822.5
3822.5/100= 38.225
x=$38.22
Answer:
about 70 years
Step-by-step explanation:
Life expectancy (e) improves by 5.7 years every 10 years, so 5.7/10 = 0.57 years per year. For t years after 2009, it can be modeled by ...
e = 0.57t +80
We want to find when that is 120:
120 = 0.57t +80
40 = 0.57t
40/0.57 = t ≈ 70.2
About 70 years from 2009, humanity may achieve a life expectancy of 120 years.